Investigation the relationship between self-esteem and breastfeeding self-efficacy in primiparous breastfeeding mothers referring to Mashhad medical centers - Malikeh Amel Barez; Nahid Maleki Saghouni; Farangis sharifi; Habibollah Esmaily; Raheleh Babazadeh (Mashhad University of Medical Sciences, 2020)
Background and Objective: Breastfeeding is an effective way to protect and promote mothers and children's health. Two important factors that affecting breastfeeding success, are self-esteem and breastfeeding self-efficacy in women. The aim of this study was to investigate the relationship between self-esteem and breastfeeding self-efficacy in primiparous breastfeeding mothers. Materials and Methods: Descriptive cross-sectional multi-stage random sampling study conducted in 2014 on 300 primiparous breastfeeding mothers referring to healthcare centers of Mashhad, Iran. Data collection was performed by demographic form, breastfeeding self-efficacy Scale and Rosenberg self-esteem scale. Data were analyzed using descriptive, inferential statistics and general linear model through SPSS version 16. Results: About demographic characteristics of participants, mother age (p= 0.001) and husband age (p < 0.001) and family income (p= 0.024) had a significant relevancy with self-esteem but infant age, husband education, residency and method of delivery weren't like that. And about relation with breastfeeding self-efficacy only method of delivery (p= 0.040) was significant. As well as, most mothers (79.3%) had high level of breastfeeding self-efficacy with a mean score of 131±13.60 and 78.7% of them had high level of self-esteem with a mean score of 27.85±3.54. Regression analysis confirmed the relationship between self-esteem and breastfeeding self-efficacy. According to the result by each score increasing of self-esteem score, breastfeeding self-efficacy score increased about 0.779.   Conclusion:  As the result indicated, maternal self-esteem is related to breastfeeding self-efficacy. These factors can help health care providers to predict length of breastfeeding, success rate of exclusive nutrition in mothers and can lead to the identification of mothers at the risk of the early breastfeeding cessation.